(untitled) (Research, Society and Development, 2021)
The interest in using low-intensity laser therapy has highly emerged among physicians and specialists in order to comprehend the potential of laser light interactions and in particular, to the biostimulation of tissues regeneration process, to control the inflammatory process and the pain. This study aims to do an integrative review to discuss the efficacy of low-intensity laser therapy in dental practice. For this, one used scientific papers from Scielo and Pubmed. One selected 19 scientific papers according to the following inclusion criteria: publications in the last 10 years, studies which evaluate the efficacy of improvement in pain, edema, trism, paresthesia and studies in vitro related to the applicability of low-intensity laser therapy. Scientific papers with more than 10 years and studies weren’t about applicability of low-intensity laser therapy weren’t considered. The results of this integrative review suggest new randomized clinical trials to prove its efficacy in clinical practice. Therefore, according to the literature was searched, low-intensity laser therapy has been efficient in different applications and in other aspects, such as tissues regeneration and the control of inflammatory processes. However, it’s necessary to carry out new studies because specific researches to evaluate the efficacy of laser therapy in pain, edema, trism and paresthesia are scarce and they demand specific protocols in their use.